2017
DOI: 10.1364/oe.25.005962
|View full text |Cite
|
Sign up to set email alerts
|

Flexoelectric in-plane switching (IPS) mode with ultra-high-transmittance, low-voltage, low-frequency, and a flicker-free image

Abstract: The demands for a power-saving mode for displaying static images are ubiquitous not only in portable devices but also in price tags and advertising panels. At a low-frequency driving in liquid crystal displays (LCDs) for low-power consumption, the flexoelectric effect arises even in calamitic liquid crystals and the optical appearance of this physical phenomenon is found to be unusually large, being noticed as an image-flickering. Although the inherent integrated optical transmittance of in-plane switching (IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…In order to use a low driving frequency to save energy, the image flickering problem must be solved. [9][10][11][12][13][14] In a previous paper, we showed that ionic effect and flexoelectric effect are the 2 factors responsible for the image flickering in FFS LCD. 15 Ions may cause 2 problems.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In order to use a low driving frequency to save energy, the image flickering problem must be solved. [9][10][11][12][13][14] In a previous paper, we showed that ionic effect and flexoelectric effect are the 2 factors responsible for the image flickering in FFS LCD. 15 Ions may cause 2 problems.…”
Section: Introductionmentioning
confidence: 97%
“…However, if the driving frequency is reduced, there is a problem that the brightness of the display may change with time, a phenomenon known as image flickering. In order to use a low driving frequency to save energy, the image flickering problem must be solved . In a previous paper, we showed that ionic effect and flexoelectric effect are the 2 factors responsible for the image flickering in FFS LCD .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hands, LCDs have some advantage in making high resolution over 1000 ppi but have some disadvantage in displaying moving pictures because its response time is relatively slow compared to the emissive type displays and still have difficulty in achieving high resolution over 2000 ppi. LCDs for VR displays are based on fringe-field switching (FFS) mode because of its high aperture ratio, high transmittance, low operation voltage and touch-screen tolerance [2][3][4][5][6]. To achieve fast response time in FFS mode or in-plane switching (IPS) mode many approaches are introduced.…”
Section: Introductionmentioning
confidence: 99%
“…The flexoelectric effect is a phenomenon, which is a coupling between electric polarization and mechanical distortion. According to Meyer's analysis, the polarization induced by flexoelectric effect can be determined as P f = e 11 n( •n)+e 33 n ( n), where e 11 and e 33 are splay and bend flexoelectric coefficients, respectively, and n is a unit vector of LC orientation [11][12][13][14][15]. Fig.…”
Section: Introductionmentioning
confidence: 99%